Nanocrystalline TiO2 with enhanced photoinduced charge separation as catalyst for the phenol degradation - Carmen Canevali; Franca Morazzoni; Roberto Scotti; Ignazio Renato Bellobono; Marco Giusti; Marco Sommariva; Massimiliano D'Arienzo; Andrea Testino; Anna Musinu; Carla Cannas (International Journal of Photoenergy)
Nanocrystalline TiO2 catalysts based on pure rutile (R100) and a 30% of anatase and 70% of rutile (R70) were synthesized by the sol-gel method, using Pluronic PE 6400 as templating agent. Catalysts were characterized in terms of structural and morphological properties; moreover, the formation of paramagnetic charge carriers under UV irradiation was studied and related to the activity of TiO2 in the photoinduced degradation of phenol. With respect to Degussa P25, the two sol-gel catalysts show lower surface area and a wider pore size distribution. The EPR spectra recorded under UV irradiation show enhanced charge separation in the sol-gel samples, with the O− species in higher amount than in Degussa P25. This result is in agreement with the high catalytic activity of R100 sample in the photoinduced degradation of phenol, very similar to that displayed by Degussa P25 and higher than that of R70 sample.